In Vitro Antibiofilm Activity of Resveratrol against Aeromonas hydrophila - Ting Qin; Kai Chen; Bingwen Xi; Liangkun Pan; Jun Xie; Liushen Lu; Kai Liu (MDPI AG, 2023)
Aeromonas hydrophila is a Gram-negative bacterium that widely exists in various aquatic environments and causes septicemia in fish and humans. Resveratrol, a natural polyterpenoid product, has potential chemo-preventive and antibacterial properties. In this study, we investigated the effect of resveratrol on A. hydrophila biofilm formation and motility. The results demonstrated that resveratrol, at sub-MIC levels, can significantly inhibit the biofilm formation of A. hydrophila, and the biofilm was decreased with increasing concentrations. The motility assay showed that resveratrol could diminish the swimming and swarming motility of A. hydrophila. Transcriptome analyses (RNA-seq) showed that A. hydrophila treated with 50 and 100 μg/mL resveratrol, respectively, presented 230 and 308 differentially expressed genes (DEGs), including 90 or 130 upregulated genes and 130 or 178 downregulated genes. Among them, genes related to flagellar, type IV pilus and chemotaxis were significantly repressed. In addition, mRNA of virulence factors OmpA, extracellular proteases, lipases and T6SS were dramatically suppressed. Further analysis revealed that the major DEGs involved in flagellar assembly and bacterial chemotaxis pathways could be regulated by cyclic-di-guanosine monophosphate (c-di-GMP)- and LysR-Type transcriptional regulator (LTTR)-dependent quorum sensing (QS) systems. Overall, our results indicate that resveratrol can inhibit A. hydrophila biofilm formation by disturbing motility and QS systems, and can be used as a promising candidate drug against motile Aeromonad septicemia.